METHODS AND MEANS OF FORMING INTERCULTURAL COMPETENCE IN TEACHING ENGLISH IN THE CONTEXT OF DISTANCE LEARNING - Menlimuratova, Elmira Azatovna (SCIENCE and SOCIETY, 2026)
This article discusses the methods and tools for developing intercultural competence in English language teaching through distance learning. These methods can also be structured hierarchically. The principles of cultural diversity and cultural opposition will be considered principles of the same level, as they are implemented in the selection of learning content and directly reveal the methodology of language teaching for the purpose of developing intercultural competence.